The impact of risk management on procurement performance through SSC within (ADNOC) in UAE: A proposed framework - AlQubaisi, Ahmed Jumaa Saeed Naser; Emran, Nurul Akmar (ASR Research India, 2022)
Currently, we live in an increasingly uncertain world that can be a threat to any business, but it can also be a source of leverage and opportunity for new ventures. Risk Management (RM) recognises that current decisions and actions can have an impact on the future and is concerned with identifying opportunities and threats.Thepurpose for this research was to assess theimpact of impact of risk management on sustainable supply chain and procurement performancewithin Abu Dhabi National Oil Company (ADNOC) inUAE.The study came to the conclusion that (ADNOC) has adopted some of the e-procurement applications, despite the difficulties that have arisen as a result of the adoption. Furthermore, the role of sustainable supply chain (SSC) in mediating the relationship between risk management and procurement performance has been confirmed. A number of additional details and important implications have been discussed throughout this study. It is hoped that the findings will assist practitioners and managers in making appropriate decisions when implementing RM, SSC, and excellence practises in their organisations in order to achieve maximum strong excellence while remaining competitive in the market. As a result, this study recommends that risk management practises be implemented more widely. It also recommends that the procurement mechanism be reviewed in order to improve the collection of adequate and accurate data for use in the risk pricing and evaluation processes.